Reaping what they sow - Abd Razak, Dzulkifli (2005)
Leaders who commit troops to wars have failed to weigh the human costs. This lack of leadership is worrying. YESTERDAY a mammoth peace rally was held in Kuala Lumpur. It marked another tragic consequence of war, commemorating the 60th anniversary of the tragic twincity bombing, beginning with Hiroshima on Aug 6 and Nagasaki three days later. Hundreds of thousands of lives were wasted and the death toll is still climbing even today, caused by atomic radiation. The twin event had so significant an impact that it cannot be easily overshadowed by the 60th anniversary of DDay two months earlier on June 6, which celebrated the beginning of the end of Nazi tyranny in Europe.